Clinical medicine.
Clinical Medicine: Pediatrics is an international, open access, peer reviewed journal which considers manuscripts on all aspects of the diagnosis, management and prevention of disorders specific to children and adolescents, in addition to related genetic, pathophysiological and epidemiological topics.